Efficacy of High-Intensity Atorvastatin for Asian Patients Undergoing Percutaneous Coronary Intervention. (September 2016) - Liu, Zhi; Joerg, Herrmann; Hao, Hengjian; Xu, Ji; Hu, Shaodong; Li, Boyu; Sang, Cheng; Xia, Jinggang; Chu, Yanyan; Xu, Dong
Background: Statins have proven cardioprotective effects, but higher doses are accompanied by various concerns and may not lead to superior clinical outcomes in Chinese/Asian populations.Objective: We designed a trial to test the efficacy of high-intensity statin therapy for the reduction of periprocedural myocardial infarction (MI) and 1-year major adverse cardiovascular events (MACEs, including cardiovascular death, spontaneous MI, unplanned revascularization) in an Asian population.Methods: A total of 798 Chinese patients with stable angina or acute coronary syndrome (ACS) were randomized to high-intensity atorvastatin (80 mg/d before percutaneous coronary intervention [PCI] and 40 mg/d thereafter for 1 year, n = 400) or moderate-intensity atorvastatin (20 mg/d for 1 year, n = 398). The primary end point was 1-year incidence of MACEs.Result: In patients with stable angina, 1-year MACE rates were not significantly different between moderate- and high-intensity groups (7.6% vs 5.7%, P = 0.53). In contrast, in patients with ACS, the 1-year MACE rate was significantly higher in the moderate- than in the high-intensity atorvastatin group (16.8% vs 10.1%, P = 0.021; adjusted hazard ratio = 1.71, 95% CI = 1.08 to 2.77, P = 0.021).Conclusions: Whereas stable angina patients derive similar benefit from moderate- and high-intensity atorvastatin therapy over the duration of 1 year after PCI, high-intensity statin therapy is superior in ACS patients.